Cycles and indeterminacy in overlapping generations economies with Stone-Geary preferences - Erkki Koskela; Mikko Puhakka (Center for Economic Studies and ifo Institute (CESifo), 2006)
We investigate dynamics in an overlapping generations economy with Stone-Geary preferences. We show that a steady state exists, and furthermore and importantly, that there can be a multitude of two cycles even though intertemporal elasticity of substitution in consumption exceeds unity.
Keywords: E21; E32; 330